PENERAPAN TEKNIK MIND MAPPING DALAM PENGAJARAN PENULISAN ESAI SASTRA BERBAHASA INGGRIS - Afina Murtiningrum (Dinamika Bahasa dan Budaya, 2019)
Some difficulties faced by students in writing a literary essay are the abilities to find the appropriate topics for the essay, develop the content paragraph structure and length in writing, and achieve cohesion and coherence. This research aims at implementing mind-mapping technique in writing a literary essay. The subjects of this research were the third semester students of English Literature Study Program at Sultan Agung Islamic University in Semarang. Observation and documentation were used to collect data in which the coherence and cohesion were analyzed. The findings show that mind-mapping technique gives significant impact to students’ abilities in writing a literary essay.